7 Producing data-driven tools. Issue Volume 23:Issue Supplement 1(2018) (June 2018) - Goldacre, Ben; Bacon, Seb; Curtis, Helen; Croker, Richard; DeVito, Nicholas; Walker, Alex; Wartolowska, Karolina
Abstract : Objectives: EBM DataLab is a team that aims to produce tools from data, rather than just academic publications. We have a multidisciplinary approach that combines the skills of software engineers, clinicians and academics. In this workshop we will give an overview covering how to make effective interactive services driven by data, through: Providing an overview of the software and services which can be used to create your own data–driven tools. Demonstrating examples from the work of the EBM DataLab. Providing an opportunity for attendees to discuss their own ideas or experiences related to data–driven tools. Method: In this session you will learn the very basics about a range of useful software and services including Python, pandas and iPython notebooks, GitHub, Google Analytics, Google Sheets, Google Forms, API's (for Scopus, PubMed, and Web of Science), SQL databases such as BigQuery and Postgres, and graphical tools such as Tableau and d3. We will demonstrate the creative use of these tools with worked examples from our recent output including the Retractobot, various trials trackers, OpenPrescribing long term trends, the Drug Tariff explorer, and more. Results: Attendees should leave this workshop with a better grasp of how to identify user needs, select the appropriate software or services for the job, design tools to be deliverable and impactful, manage the development cycle from prototyping to launch, and carry out the basic process of user testing. Conclusions: Simple yet engaging presentation of data that allows people to act on it can be a critical step in disseminating evidence and improving quality of care. Live updating dynamic tools can keep information at the cutting-edge and provide a platform that provides real and enduring value to users. There are great resources available that can allow researchers to quickly and efficiently turn their findings into public-facing tools. We hope this workshop will empower attendees to begin presenting and sharing their data in new and effective ways in order to promote positive change in their respective fields.